World trade in oil with focus on OPEC+ - Provazník, Jakub (2025)
The aim of the thesis was to map the long- term and short-term trends in the global oil market with focus on the OPEC + in international trade with it. Moreover, two research questions was elaborated on and it was how does the OPEC + react to current trend of environmental change and what is the significance of OPEC + in the Russia - Ukraine war. The first part is the theoretical one, focusing on what crude oil is and what are main refined products, types of crude oil, drilling and refining and brief introduction of OPEC. In the second part, there is an examination of world trade in crude oil, focusing on main trends in the oil market, main traders and price. The last part is solely focused on OPEC +, showing what it is, its significance in the world trade in oil and in the Russia - Ukraine war and its reactions to the environmental changes.